Analisis Kualitas Produk Dan Promosi Terhadap Kepuasan Konsumen Produk Holland Bakery - Purba, Tiurniari (ADAI Kepri, 2022)
The aim of this research is to determine the effect of product quality and promotion on customer satisfaction Holland Bakery Product. To determine the sample of researchers using the Slovin formula with the number of respondents 287, sampling technique using simple random sampling, for processing data this study uses SPSS 22. Product quality variables significantly influence the value of 0.038 <0.05 alpha and t count value of 2.085 > 1,968 t tables. Promotional variables significantly influence the value of 0,000 < 0.05 alpha and the value of t arithmetic 32.187 > 1.968 t table. Product quality and promotion simultaneously affect the f table value 639,339 > 2.64 with a significant value of 0,000 < 0.05.